Asymmetric Steklov problems with sign changing weights - DOUMATE, TELE JONAS; LEADI, LIAMIDI ARÈMOU; MARCOS, ABOUBACAR (My University, 2015)
We study two asymmetric Steklov problems with indefinite weights involving the p-Laplacian operator. We prove the existence of a first nontrivial eigenvalue for the first problem and the second one serves as an application in the description of the beginning of the Fučik spectrum with weights. We thereby extend several known results related to these problems.
Keywords: p-Laplacian plus a potential; Asymmetric; Nonprincipal eigenvalue Steklov; boundary condition; Weight; Fučik spectrum.